MEASUREMENT OF AMMONIUM IN HAEMOLYMPH AND MALPIGHIAN TUBULE SECRETION IN DROSOPHILA MELANOGASTER: APPLICATION OF A NOVEL AMMONIUM-SELECTIVE MICROELECTRODE - Browne, Austin A. (My University, 2012)
The transport of ammonia by various tissues throughout the body is of fundamental importance for nitrogen excretion in invertebrates, yet sites and mechanisms of ammonia transport are not presently well understood. In this thesis a novel ammonium-selective microelectrode was developed using the ionophore TD19C6, which is approximately 3800-fold more selective for NH4+ than Na+ compared with the 100-fold difference of nonactin used in previous microelectrodes. We investigated the accuracy of the ammonium microelectrode in solutions simulating Drosophila haemolymph (25 mM K+) and secreted fluid (120 mM K+). In haemolymph-like solutions, ammonium could be measured down to about 1 mM, with an error of 0.5 mM, while in secreted fluid-like conditions ammonium could be determined to within 0.3 mM down to a level of 1 mM NH4+ in the presence of 100 to 140 mM K+. These results suggested that the ammonium microelectrode could be used to measure ammonium in the presence of physiological levels of potassium, unlike previous studies. We also quantified ammonium secretion by the Malpighian (renal) tubules of larvae. Ammonium concentrations of secreted fluid were consistently equivalent to or above ammonium concentrations of bathing salines. With a lumen-positive transepithelial potential, these results suggested an active secretory mechanism for ammonia transport. Under conditions of low K+ concentrations, the ability of the tubules to concentrate ammonium in secreted fluid was significantly enhanced, indicating some level of competition between NH4+ and K+ for common transporters. The new ammonium-selective microelectrode is sufficiently sensitive to detect ammonium at the picomol level.
Keywords: microelectrode; Drosophila; ammonia; ammonium; Malpighian tubule; selectivity coefficient; Zoology; Zoology